The wisdom of China and India - 20160731 frey50; Yutang, Lin (Unknown The Modern Library of the World's Best Books)
A collections of writings from China and India, including religious, humor, poetry and sketches of life.
Keywords: Cultural wisdom - Collection. -- Literature - China -- Literature - India -- Religion. -- Fables. -- Parables. -- Philosophy; Sacred books; China - India; Collection